José María Arguedas y el indigenismo revolucionario guatemalteco (1951-1961) - Palencia Frener, Sergio (Pontificia Universidad Católica del Perú, 2025)
This paper explores José María Arguedas’ thoughts about the Indigenista policies during the October Revolution (1944-1954) in Guatemala. After listening to the Guatemalan anthropologist Antonio Goubaud Carrera in 1951, Arguedas and other Latin American intellectuals discussed the Indigenista research and policies in Guatemala. Drawing from two publications by Arguedas in 1953 and 1959, and archival research at the Guatemalan National Indigenista Institute and the International Labour Organization (ILO), this essay studies José María Arguedas’ interest and reflections about Goubaud and the Indigenista policies led by Guatemalan anthropologist Joaquín Noval. This article examines Arguedas research on “folk art” and “popular art” in Peru in relation to the Guatemalan revolutionary Indigenismo and his later critique of the commodification and technification of folk creation. By reconstructing biographical, political, and academic aspects in Arguedas’ life, this essay ultimately analyzes his decision to carry on ethnographic fieldwork in Guatemala in 1961. Overall, this paper discusses the little-known relationship between Arguedas and Guatemala, a standpoint that decentralizes the history of anthropology and Latin American intellectual networks.

Este trabajo explora por primera vez las reflexiones de José María Arguedas sobre las políticas indigenistas de la Revolución de Octubre (1944-1954) en Guatemala. En 1951, tras escuchar al antropólogo guatemalteco Antonio Goubaud Carrera, Arguedas y otros intelectuales latinoamericanos quedaron impresionados por las investigaciones y políticas indigenistas de Guatemala. Con base en dos escritos de Arguedas de 1953 y 1959, así como a archivos del Instituto Indigenista Nacional en Guatemala y de la Organización Internacional del Trabajo (OIT), este trabajo traza el interés y discusión de José María Arguedas sobre la ponencia de Goubaud y la línea indigenista dirigida por el antropólogo guatemalteco Joaquín Noval. Con base en la propia investigación de Arguedas sobre el «arte folklórico» o «arte popular» del Perú, este estudio recoge las perspectivas de Arguedas acerca del indigenismo revolucionario guatemalteco como, también, su eventual crítica a la tecnificación y mercantilización de la creación popular. Con base en aspectos biográficos, políticos y académicos de Arguedas, este trabajo reconstruye su decisión de hacer trabajo etnográfico en Guatemala en 1961. Así pues, se aborda la poco conocida relación de Arguedas con Guatemala, hecho que aporta en descentralizar la historia de la antropología y redes intelectuales latinoamericanas.
José María Arguedas and the Guatemalan Revolutionary Indigenism (1951-1961)
Keywords: Indigenism; Folklore; Revolution; Peru; Guatemala; Indigenismo; Folklore; Revolución; Perú; Guatemala; Arte popular; https://purl.org/pe-repo/ocde/ford#5.04.03